Review on the Use of Black Pepper (Piper spp.) and Red Pepper (Capsicum spp.) as Grain Protectants - Pegalepo, Esther; Bokonon-Ganta, Aimé H.; DOSSOU, JOSEPH; SIE, MOUSSA; Pegalepo, Angèles Ndogho (My University, 2018)
The use of synthetic insecticides to store grain is very common upon the injuries they caused to human being and the pollution of the environment. Many studies have been made for controlling pests of grain with botanical insecticides. However, some of these plants with insecticide effects are not edible by human beings and can also cause injuries. This review is the compilation of results on the use of spices like Capsicum spp. and Piper spp. to control insect pest with their toxicity and repellent effects, antifeeding effect and the inhibition of the reproduction
Keywords: Black pepper; Grain protectant; Red pepper